Differences in Use of the Learning Model Jigsaw Type Cooperative with Talking Stick on Student Learning Results Class X OTKP SMKS Budisatrya Medan - Mita Indria Saputri; Dalmi Iskandar Sultani (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
Research Title: Differences in the Use of Jigsaw and Talking Stick Cooperative Learning Models on Archival Learning Outcomes of Class X OTKP Students at Budisatrya Private Vocational School in Medan for the 2021-2022 Academic Year. The purpose of the study was to determine the differences in the use of the Jigsaw Cooperative learning model with the Talking Stick on Archival learning outcomes. The research method uses Post-test Only Control Design. The population in the study were all students of class X OTKP SMKS Budisatrya Medan. The research sample is class X OTKP 1 and X OTKP 2 totaling 40 students. The research instrument used was interviews, tests, and documentation. The results obtained that the tcount value is greater than ttable, where tcount = 2.272 > ttable = 1.685. Thus, H0 is rejected and Ha is accepted. Conclusion: there are differences in the use of the Jigsaw Cooperative learning model with the Talking Stick on student archive learning outcomes.